1984
DOI: 10.1148/radiology.150.2.6691094
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular outflow obstruction and necrotizing enterocolitis.

Abstract: Two neonates had unusually rapid development of necrotizing enterocolitis within 24 hours of birth. Both patients had decreased systemic perfusion secondary to aortic atresia. Onset of either clinical or radiographic manifestations of necrotizing enterocolitis in the first day of life should alert one to the possible presence of severe left ventricular outflow obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As a consequence, the decrease in intestinal blood supply was suspected to increase the incidence of NEC in patients with left ventricular outflow obstruction or aortic atresia and UAC [7][8][9]. As a consequence, the decrease in intestinal blood supply was suspected to increase the incidence of NEC in patients with left ventricular outflow obstruction or aortic atresia and UAC [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the decrease in intestinal blood supply was suspected to increase the incidence of NEC in patients with left ventricular outflow obstruction or aortic atresia and UAC [7][8][9]. As a consequence, the decrease in intestinal blood supply was suspected to increase the incidence of NEC in patients with left ventricular outflow obstruction or aortic atresia and UAC [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Van Bel et al [10] found a decrease of mean blood flow velocities in the SMA following indomethacin therapy and speculated that indomethacin led to a decreased intestinal perfusion, similar to its action on cerebral blood flow. Reduced mesenteric blood flow is suspected to increase the risk of NEC [8,9]. PSFV and mean systolic blood flow velocities in the SMA increase after feeding, depending on the amount of milk fed [11].…”
Section: Discussionmentioning
confidence: 99%
“…The only known predisposing factors to NEC are prematurity 3 and congenital heart disease. 4 Epidemic NEC occurs in clusters of both time and location. Although NEC occurs mostly in premature infants weighing less than 1,000 g, it also occurs in full-term neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel ischemia has also been proposed as a pathogenic factor for NEC, and the congenital heart disease, particularly left-sided obstructive lesions (such as those seen in the present case) that can lead to decreased systemic perfusion, is a well-described predisposing factor for NEC in full-term neonates. 4 It was proposed that perinatal asphyxia triggers an alteration in perfusion that results in ischemia of the gut but preservation of blood flow to the brain, heart, and kidneys. Redistribution of cardiac output away from the splanchnic circulation was assumed to lead to intestinal hypoxia and later to bowel necrosis.…”
Section: Discussionmentioning
confidence: 99%